2011
DOI: 10.1111/j.1582-4934.2010.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective CXCR4 expression in aged bone marrow cells impairs vascular regeneration

Abstract: The chemokine stromal cell-derived factor-1 (SDF-1) plays a critical role in mobilizing precursor cells in the bone marrow and is essential for efficient vascular regeneration and repair. We recently reported that calcium augments the expression of chemokine receptor CXCR4 and enhances the angiogenic potential of bone marrow derived cells (BMCs). Neovascularization is impaired by aging therefore we suggested that aging may cause defects of CXCR4 expression and cellular responses to calcium. Indeed we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
(59 reference statements)
2
22
0
Order By: Relevance
“…In the present study, we demonstrate that the basal Sca1 +/CXCR4 + progenitor cell levels in the bone marrow are not attenuated with age. In line with other studies [33,34], age-dependent depletion of progenitor cells is likely to be specific to a subpopulation of intermediate vascular progenitor cells (CD31 +/CD45 −) whereas the primitive progenitor subpopulations (Sca1+/c-kit+/lin−) are not affected by age. In fact, higher basal levels of bone marrow Sca1 +/CXCR4 + BMDACs were found in aged mice prior to ischemia.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we demonstrate that the basal Sca1 +/CXCR4 + progenitor cell levels in the bone marrow are not attenuated with age. In line with other studies [33,34], age-dependent depletion of progenitor cells is likely to be specific to a subpopulation of intermediate vascular progenitor cells (CD31 +/CD45 −) whereas the primitive progenitor subpopulations (Sca1+/c-kit+/lin−) are not affected by age. In fact, higher basal levels of bone marrow Sca1 +/CXCR4 + BMDACs were found in aged mice prior to ischemia.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to earlier studies (Waterstrat and Van Zant. 2009;Zediak et al 2007;Shao et al 2011), there were more myeloid lineage cells than lymphoid lineages cells in aged BM. Consequently, we sorted out B220 + , CD11b + , and Ter119 + cells which had greater differences and a higher proportion from BM A to coculture with the same bone fragments, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Min et al found that the number of common lymphoid progenitors (CLPs), pro-B cells, and pre-B cells in BM from aged mice was significantly less than that in BM from young mice (Min et al 2006). However, the number of Gr1 + /CD11b + cells in BM from aged mice is higher than that in BM from young mice (Shao et al 2011). These studies indicate that aging is associated with intrinsic HSC changes as well as changes in the microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…17 During flow cytometry analysis, fluorescence of samples was monitored for a 30-second baseline, then sample aspiration was briefly paused, and 2 μl PBS, or CaCl 2 (final concentration 1mM), or CaCl 2 plus Ionomycin (final concentration 10μM) in Ca 2+ flux assay buffer were added into the samples. Ca 2+ influx was determined by measuring the change in green fluorescence intensity of the cells over time.…”
Section: Methodsmentioning
confidence: 99%
“…17 Since ApoE −/− mice spontaneously develop hypercholesterolemia and atherosclerotic lesions and have significantly shorter lifespan than wild type mice 18 , we hypothesize that atherogenic ApoE −/− mice have earlier and more severe CXCR4/SDF-1 defects than their wild type (WT) counterparts. Our rationale for the present studies is that atherosclerosis generates an aging phenotype in ApoE −/− mice and this may be associated with correspondingly reduced numbers and functions of CXCR4-positive BM progenitors.…”
Section: Introductionmentioning
confidence: 99%